Introducing novel type of human DNA markers for forensic tissue identification: DNA copy number variation allows the detection of blood and semen. (September 2018) - Zubakov, Dmitry; Chamier-Ciemińska, Joanna; Kokmeijer, Iris; Maciejewska, Agnieszka; Martínez, Pilar; Pawłowski, Ryszard; Haas, Cordula; Kayser, Manfred
Highlights: Novel type of DNA markers introduced for forensic tissue identification. Copy number variation (CNV) DNA markers identified for blood and semen. CNV qPCR assays show high sensitivity, specificity and coping with degraded DNA. CNV qPCR products represent suitable input material for forensic STR-profiling. Abstract: Establishing the cellular or tissue-type origin of human biological traces found at crimes scenes is forensically relevant, as it allows evaluating the crime relevance of such traces and enables reconstructing the sequence of crime events. Messenger RNA and micro RNA markers are useful for forensic tissue identification, but provide challenges for linking RNA-identified cell/tissue types with DNA-identified trace donors, especially in mixed traces. DNA methylation markers overcome this problem, but provide technical challenges due to the DNA treatment required by most analysis methods. Here we introduce a novel type of DNA markers for forensic tissue identification analysed without prior DNA treatment, namely copy number variation (CNV). Using genome-wide CNV screening followed-up by targeted qPCR confirmation, and using qPCR analysis of additional CNV-like candidate DNA markers, in samples of several individuals from all commonly encountered forensically-relevant tissue types, we identified DNA markers specific for blood and semen, respectively. Preliminary forensic validation testing demonstrates that the developed qPCR assays are highly sensitive – delivering positive results down to picogram level of input DNA, specific, and can cope well with degraded DNA, providing suitable prerequisites for forensic applications. Moreover, we exemplified that using the CNV qPCR products as input material for subsequent forensic STR analysis delivered full STR profiles, opening-up new avenues of using the same DNA aliquot for both forensic purposes, tissue and individual identification. Provided additional forensic validation studies, we envision the application of these novel DNA markers for forensic tissue identification in future forensic casework. Such CNV markers are particularly useful for tissue identification in old/cold cases, where aged/old DNA extracts are available that contain no RNA and are not suitable for DNA methylation analysis due to limited DNA quantity and quality.